2000
DOI: 10.1115/1.1313531
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Offshore Platforms Under Subsidence—Part II: Analysis and Results

Abstract: An assessment of three offshore platforms in the Valhall field of the North Sea is described in this paper. Ultimate strength and reliability analyses were performed for the jacket-type platforms for four levels of sea floor subsidence. The nonlinear structural models of the platform elements, joints, and associated soil-structure interaction are summarized in a companion paper by Gebara et al., 2000, “Assessment of Offshore Platforms Under Subsidence—Part I: Approach,” ASME J. Offshore Mech. Arct. Eng., 122, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It is suggested that the component method [45,46] or computational fluid dynamic method [28,[47][48][49] are to be utilized to calculate the wave-in-deck load in order to reduce the conservatism of the silhouette method. The risk of platform damage may be reduced via modification such as localized protection or relocation of exposed sensitive equipment or via procedures such as production shut-in and temporary evacuation during storm season [59,60]. Another method that was successfully performed was by jacking-up the platform in order to increase the air gap of platform [61].…”
Section: Probability Of Failurementioning
confidence: 99%
“…It is suggested that the component method [45,46] or computational fluid dynamic method [28,[47][48][49] are to be utilized to calculate the wave-in-deck load in order to reduce the conservatism of the silhouette method. The risk of platform damage may be reduced via modification such as localized protection or relocation of exposed sensitive equipment or via procedures such as production shut-in and temporary evacuation during storm season [59,60]. Another method that was successfully performed was by jacking-up the platform in order to increase the air gap of platform [61].…”
Section: Probability Of Failurementioning
confidence: 99%
“…Pile foundation is widely used in these structures. And piles bear the loads including drag force and lift force under the wave and current and usually are destroyed by wave-current flow [1,2]. Indoor model experiments were made to study the influence of different flow velocities in wave-current flow on loads of a single pile and the change of the key coefficients.…”
Section: Introductionmentioning
confidence: 99%